Software Sistem Pelaporan Akuntansi Koperasi (Silakop) Sebagai Solusi Pencatatan dan Pelaporan Keuangan Koperasi Wanita - Syaiful Hidayat, Ujang; Siwidyah Desi Lastianti; Yanna Eka Pratiwi; Indra Wijayanto; Ida (Universitas Merdeka Surabaya, 2023)
This article discusses women's cooperatives, which have an important role in efforts to empower women and help improve the welfare of their members. However, women's cooperatives face financial reporting problems and a lack of knowledge and skills in preparing financial reports in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP). This study aims to design and develop accounting software that can provide solutions to the problems of recording and reporting finances for women's cooperatives. This action research uses a qualitative approach, carried out in the cities of Malang and Surabaya in the period October-November 2022, with data collected through interviews, observations and financial documents. The result of this research is a cooperative accounting reporting software (SiLaKop) that has been used in several KopWans in the City and Regency of Malang.